Social Media Social Capital, Offline Social Capital, and Citizenship: Exploring Asymmetrical Social Capital Effects. (2nd January 2017) - de Zúñiga, Homero Gil; Barnidge, Matthew; Scherman, Andrés
Abstract : In pursuit of a healthier and participatory democracy, scholars have long established the positive effects of social capital, values derived from resources embedded in social ties with others which characterize the structure of opportunity and action in communities. Today, social media afford members of digital communities the ability to relate in new ways. In these contexts, the question that arises is whether new forms of social capital associated with the use of social media are a mere extension of traditional social capital or if they are in fact a different construct with a unique and distinct palette of attributes and effects. This study introduces social media social capital as a new conceptual and empirical construct to complement face-to-face social capital. Based on a two-wave panel data set collected in the United States, this study tests whether social capital in social media and offline settings are indeed two distinct empirical constructs. Then, the article examines how these two modes of social capital may relate to different types of citizenship online and offline. Results show that social media social capital is empirically distinct from face-to-face social capital. In addition, the two constructs exhibit different patterns of effects over online and offline political participatory behaviors. Results are discussed in light of theoretical developments in the area of social capital and pro-democratic political engagement.